Empire’s Informal Ties: Pioneer Anthropologists in Davao, 1904–1916 - Dacudao, Patricia Irene (Archīum Ateneo, 2020)
The five Americans who studied the indigenous Bagobo people in Davao from 1904 to 1916 did not adhere to the evolutionary anthropology championed by colonial administrator Dean Worcester. Their fieldwork, being either mostly self-supported or through the privately funded Field Museum of Natural History, was also financially independent of the government. This article studies their personal, academic, and professional quests in the context of museum collections, party politics, and changes in the discipline of anthropology. The circumstances of their visits and subsequent publications on Davao show that these pioneers pursued anthropology with a different direction, away from state stereotypes and imperial entanglements.